Effects of leakage delays and impulsive control in dissipativity analysis of Takagi–Sugeno fuzzy neural networks with randomly occurring uncertainties. Issue 8 (May 2017) - Samidurai, R.; Senthilraj, S.; Zhu, Quanxin; Raja, R.; Hu, Wei
Abstract: In this paper, dissipativity analysis problem is investigated for T-S fuzzy neural networks with leakage delays and impulsive effects. Sufficient conditions for the dissipativity criteria are derived by using Lyapunov–Krasovskii functional having triple and four integral terms with free weighting matrix method. The obtained results are dependent on the the leakage delay and upper bound of time-varying delay. Moreover, some comparisons are made to contrast to some of existing results about strictly ( Q, S, R ) − ϑ -dissipativity for the concerned neural networks. Finally, some numerical examples and their computer simulations are given to show the effectiveness of the proposed criteria.